Genetic Improvement and Selective Breeding in Fish Aquaculture: Recent Advances - Ibrahim, Abdallah (International Journal of Aquatic Research and Environmental Studies, 2026)
Aquaculture is one of the most rapidly expanding food production industries in the world, providing a growing share of animal protein in the world's diet. Sustaining this growth requires continuous improvements in productivity, resource-use efficiency, and resilience to environmental and disease-related challenges. Selective breeding has become an integral part of modern aquaculture and is a key method for achieving permanent and cumulative improvements in economically significant attributes such as growth rate, feed conversion ratio, resistance to disease and infection, reproductive capacity, product quality, and environmental adaptability. The use of marker-assisted selection, quantitative trait locus mapping, genome-wide association studies, genomic selection, and, more recently, genome editing, has revolutionized traditional breeding programs over the last ten years. These have significantly contributed to the more precise and efficient breeding programs and the faster genetic improvement in economically valuable fish species. This narrative review aims to summarize advances in genetic improvement and selective breeding in fish aquaculture, with a particular focus on genomic technologies and their applications in Atlantic salmon (Salmo salar), Nile tilapia (Oreochromis niloticus), common carp (Cyprinus carpio), and rainbow trout (Oncorhynchus mykiss). The review further covers current limitations, such as limited genetic diversity, infrastructure constraints, economic considerations, and ethical concerns with advanced breeding technologies. Lastly, key knowledge gaps and future opportunities are identified to develop sustainable, climate-resilient, and genetically better aquaculture systems for future global food needs.
Keywords: selective breeding, fish aquaculture, genetic improvement, genomic selection, marker-assisted selection, sustainable aquaculture